KEMAMPUAN PEMECAHAN MASALAH SISWA PADA MATERI PERBANDINGAN DITINJAU DARI ADVERSITY QUOTIENT - M Wahab; Ade Mirza; Hamdani Hamdani (Jurnal AlphaEuclidEdu, 2022)
This research was based on the results of pre-research showed that students’ problem-solving abilities were still low, especially in comparison materials. Problem-solving abilities can be influenced by many factors, one of which is adversity quotient. One of the first steps that can be done to explore students’ problem-solving skills is to discuss how the problem-solving abilities that students currently have. The goal of this research is to know and to describe students’ problem-solving skills in comparison materials in class VII. Descriptive method is used in this study. The students of class VIII C of SMP Negeri 1 Teluk Keramat for the 2021/2022 school year were the subject in this study. Then they were sampled by 3 people from the climber type ada 3 people from the camper type. The data.collection.tools.in.this.study are subjective written tests in the form of essays and interview guidelines. The results revealed that in general, students’ math problem-solving skills were relatively low with an average score of 58,6 test scores. In this study, students who were able to complete all indicators of problem-solving.ability by 50% and students who had not been able to complete all indicators of problem-solving ability by 50%.